Tofacitinib 5 mg Twice Daily in Patients with Rheumatoid Arthritis and Inadequate Response to Disease-Modifying Antirheumatic Drugs: A Comprehensive Review of Phase 3 Efficacy and Safety. Issue 3 (April 2019) - Bird, Paul; Bensen, William; El-Zorkany, Bassel; Kaine, Jeffrey; Manapat-Reyes, Bernadette Heizel; Pascual-Ramos, Virginia; Witcombe, David; Soma, Koshika; Zhang, Richard; Thirunavukkarasu, Krishan
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis (RA). We performed a comprehensive review of phase 3 studies of tofacitinib 5 mg twice daily (BID) (approved dose in many countries) in patients with moderate to severe RA and inadequate response to prior disease-modifying antirheumatic drugs. Methods: A search of PubMed and ClinicalTrials.gov identified 5 studies: ORAL Solo (NCT00814307), ORAL Sync (NCT00856544), ORAL Standard (included adalimumab 40 mg once every 2 weeks; NCT00853385), ORAL Scan (NCT00847613), and ORAL Step (NCT00960440). Efficacy and safety data for tofacitinib 5 mg BID, placebo, and adalimumab were analyzed. Results: Across the 5 studies, 1216 patients received tofacitinib 5 mg BID, 681 received placebo, and 204 received adalimumab. At month 3, tofacitinib demonstrated significantly higher 20%, 50%, and 70% improvement in American College of Rheumatology response criteria (ACR20, ACR50, and ACR70, respectively) response rates, greater improvement in Health Assessment Questionnaire-Disability Index, and a higher proportion of Disease Activity Score-defined remission than placebo. Frequencies of adverse events (AEs), serious AEs, and discontinuations due to AEs were similar for tofacitinib and placebo at month 3; serious infection events were more frequent for tofacitinib. In ORAL Standard, although not powered for formal comparisons, tofacitinib and adalimumab had numerically similar efficacy and AEs; serious AEs and serious infection events were more frequent with tofacitinib. Conclusions: Tofacitinib 5 mg BID reduced RA signs and symptoms and improved physical function versus placebo in patients with inadequate response to prior disease-modifying antirheumatic drugs. Tofacitinib 5 mg BID had a consistent, manageable safety profile across studies, with no new safety signals identified.